O ensino da língua portuguesa para os alunos surdos do ensino fundamental maior da escola municipal “Dr. Anthódio Barbosa” em Tomé Açu/PA - GONZAGA, Marlene de Nazaré da Silva (2023)
The present work was developed in a regular public primary school in the municipality of Tomé-Açu / PA, which has deaf students in its class. It aims to analyze the teaching-learning process of the Portuguese language for deaf students through the data collection through a questionnaire applied to teachers of Portuguese language and teachers of the Specialized Educational Assistance (AEE); As well as to explain the possibilities and difficulties experienced by both deaf students and teachers in what concerns the teaching of the Portuguese language to deaf students, observing the methodologies for their teaching. As a theoretical contribution to this work, we have: (1997, 2004, 2006 and 2008), Reily (2007), Goldfeld (1997), Perlin (1998), Silva (2002), MEC publications (1979, 1997, 2002) Among others of the area, as well as the most current strands currently found through readings of scientific articles and other available publications that made possible the development of the study.